Increased serum homocysteine in first episode and drug-naïve individuals with schizophrenia: sex differences and correlations with clinical symptoms - Xu Yang; Haidong Yang; Na Li; Chunyu Li; Weiye Liang; Xiaobin Zhang (BMC Psychiatry, 2022)
Abstract Background Accumulating evidence shows that homocysteine (Hcy) is implicated in the pathophysiology of schizophrenia, and plays an important role in clinical characteristics. This study evaluated the relationships between Hcy levels and clinical features in first-episode, Chinese Han, drug-naïve (FEDN) patients with schizophrenia. Methods FEDN individuals (119 with schizophrenia and 81 healthy controls matched for age, sex, education, and body mass index (BMI)) were enrolled. The serum Hcy levels were determined by enzyme cycle assay experiments. Severities of clinical symptoms were rated on the Positive and Negative Syndrome Scale (PANSS). Results FEDN individuals with schizophrenia had higher Hcy levels compared with healthy controls (F = 46.865, P < 0.001). Correlation analysis and multiple stepwise regression analyses showed that serum Hcy levels in FEDN schizophrenia individuals were positively correlated with PANSS general psychopathology subscale (r = 0.294, P = 0.001) and PANSS total score (r = 0.273, P = 0.003). No significant association was found between Hcy and age, BMI, PANSS positive subscale, and the PANSS negative subscale (all, P > 0.05). Male individuals had significantly higher serum Hcy levels than female individuals (F = 7.717, P = 0.006) after controlling for confounding factors (F = 0.759, P = 0.011). Conclusions Serum Hcy levels were increased in FEDN individuals with schizophrenia, and Hcy levels may be involved in pathophysiological mechanisms. Sex differences in Hcy levels were observed, with higher levels in male FEDN individuals compared to females.